Association between dietary antioxidant indices and glaucoma in the National Health and Nutrition Examination Survey - Li, Wenwei; Wang, Bin (Frontiers in Nutrition, 2023)
Objective: To explore the relationship between dietary antioxidant indices (DAI) and glaucoma using the data from the 2005 to 2008 National Health and Nutrition Examination Survey (NHANES).Methods: Our study comprised participants who completed the NHANES dietary intake interview and visual health questionnaire at age 40 or older. The intakes of the vitamins A, C, and E as well as of zinc, selenium, and magnesium were used to generate the DAI, which represents the overall antioxidant qualities. The self-report method for glaucoma diagnosis ( ever been told by an eye doctor ) was used. Survey logistic regression analyses were employed to investigate the association between DAI and glaucoma.Results: A total of 6128 participants were included in our study. The unadjusted model's findings revealed a negative correlation between dietary antioxidant indices and self-reported glaucoma (0.93[0.90,0.96], p<0.0001). For every unit increase in dietary antioxidant indices, the risks of selfreported glaucoma in model 1 (adjusted for age, sex, race, marital status and PIR) decreased by 5% (0.95[0.90,0.99], p=0.02). After adjusting all the covariates (model 2), the risks of self-reported glaucoma decreased by 6% (0.94[0.90,0.99], p=0.02) for each unit increase of dietary antioxidant indices. After converting DAI into classified variables (tertile), the same trend was found (p=0.001).Conclusions: In this analysis of the NHANES database, we found higher dietary antioxidant indices were associated with lower risk of glaucoma.